The Influence of Organizational Culture and Organizational Justice on Group Cohesion as Perceived by Merger and Acquisition Employees - Ismail, Maimunah; Baki, Nordahlia Umar; Omar, Zoharah (Organizations and Markets in Emerging Economies, 2018)
One of the knowledge gaps in relation to merger and acquisition (M&A) research is an analysis from the perspective of human resources, specifically the extent to which organizational culture and organization justice play a role in group cohesion of the employees. This research investigates the influence of organizational culture and organizational justice factors on group cohesion in selected M&A organizations in Malaysia. This study is driven by the Person-Environment (P-E) Fit Theory. A total of 219 respondents from the M&A organizations in the areas of Klang Valley were involved in this study in which they were identified through the cluster random sampling method. Data were analyzed using Structural Equation Modeling (SEM). This study provides insights to the theory and practice of human resource management in organizations experiencing M&A.